FcγRIII (CD16)‐mediated ADCC by NK cells is regulated by monocytes and FcγRII (CD32). Issue 11 (19th September 2014) - Bhatnagar, Nupur; Ahmad, Fareed; Hong, Henoch S.; Eberhard, Johanna; Lu, I‐Na; Ballmaier, Matthias; Schmidt, Reinhold E.; Jacobs, Roland; Meyer‐Olson, Dirk
<x xml:space="preserve">Abstract</x> Monocytes are known to engage in reciprocal crosstalk with NK cells but their influence on NK‐cell‐associated antibody‐dependent cellular cytotoxicity (ADCC) is not well understood. We demonstrate that in humans FcγRIII (CD16)‐dependent ADCC by NK cells is considerably enhanced by monocytes, and that this effect is regulated by FcγRII (CD32) crosslinking in healthy individuals. It is known that during HIV‐1 infection, NK cells are known to express low levels of CD16 and exhibit reduced ADCC. We show that immune regulation of CD16‐mediated NK‐cell cytotoxicity by monocytes through CD32 engagement is substantially disturbed in chronic progressive HIV‐1 infection. Expression of activating isoform of CD32 represented a compensatory mechanism for reduced expression of CD16 on NK cells during HIV‐1 infection. As a result, the regulation of NK‐cell‐associated ADCC by monocytes is skewed and eventually constitutes a novel factor that contributes to HIV‐1‐associated immune deficiency, dysregulation and pathogenesis. Our data therefore provide evidence, for the first time, that in humans monocytes act as a rheostat for FcγRIII‐mediated NK‐cell functions maintaining a well‐balanced immune response.